Hoaks Tentang Pesantren di Media Sosial dan Upaya Menangkalnya - Annisa Najmagita Andhara; Siti Ulandari; Faiz Fikri Al Fahmi; Qois Ahmad Syauqi; Amara Suryadayana; Ahda Sabila (ISME : Journal of Islamic Studies and Multidisciplinary Research, 2025)
Pesantren, as indigenous Islamic educational institutions in Indonesia, play a strategic role in character building, moral strengthening, and maintaining social stability. However, in the era of digital disruption, pesantren are vulnerable to hoaxes and misinformation that can negatively influence public perception. This study aims to map the typologies and motives of hoaxes targeting pesantren, analyze their impact on socio-religious image, and explore mitigation strategies through digital literacy grounded in Islamic values and community collaboration. The research employs a qualitative social approach using literature review, thematic analysis, and critical discourse analysis, with source triangulation to ensure data validity. The findings indicate that hoaxes targeting pesantren manifest in various forms: ideological-political, moral-social, economic-financial, and theological. The resulting impacts are multidimensional, including social stigmatization, psychological pressure on students and educators, political polarization, and threats to national stability. Mitigation efforts are carried out through digital literacy, media ethics, digital da'wah, and community collaboration. These findings underscore the importance of Islamic values-based digital literacy in building a healthy information ecosystem and strengthening socio-religious resilience.